Fagpersonells forståelse av økt registrert tvangsbruk overfor personer med utviklingshemming - Dragsten, Frode; Søndenaa, Erik (Nordisk tidsskrift for helseforskning, 2015)
Norwegian legislation concerning restraint measures in the care and treatment to people with intellectual disability (ID) has been established since 1999. This study examined the social workers’ explanations for the increased number of people with ID being legally restrained since 1999. This article discussed both staff and the supervisors perspectives of the increase. Although an increasingly number of people with ID are treated by restraint measures, respondents (n = 206) report that care services has evolved in a positive direction. The strong increase is explained by a higher ethical awareness and changes in legal rules along the way. When asked about the future development, most respondents expect a continuing growth in the number of people with ID treated with the use of restraint measures.